Day that shook the world [videorecording] : a complete series one (U.K : BBC, 2005)
These are the seismic moments in history - human tragedies, scientific breakthroughs or era-defining events - that have profoundly affected how the world thinks and acts. Exciting, dramatic, gripping and illuminating, each episode in the series builds a compelling picture of events and sheds newlight on the 'landmark of the time.'
Disc 3
Keywords: World history -- Early works to 1800.